Prediabetes Burden in Nigeria: A Systematic Review and Meta-Analysis - Bashir, Musa Ado; Yahaya, Anas Ibrahim; Muhammad, Mukhtar; Yusuf, Ashiru Hassan; Mukhtar, Isyaku Gwarzo (Frontiers in Public Health, 2021)
Prediabetes is a borderline glycemic status associated with both higher incident cardiovascular disease as well as higher risk of progression to diabetes. There is a rising burden of diabetes and prediabetes globally. This study aims to estimate the burden of prediabetes in Nigeria. Online searches of Google Scholar, PubMed and Scopus were conducted and studies selected based on predefined criteria. 15 studies consisting of 14206 individuals conducted between 2000 and 2019 were included in the meta-analysis with studies using American Diabetic Association (ADA) and World Health Organization (WHO) criteria pooled separately. The pooled prevalence of prediabetes in Nigeria was found to be 13.2% (95% CI: 5.6%-23.2%, I2 = 98.4% ) using the ADA criteria and 10.4% (95% CI: 4.3%-18.9%, I2 = 99.2% ) using the WHO criteria. According to the latest data by the United Nations(1), this translates to estimated 15.8 million and 12.5 adult prediabetic individuals in Nigeria using the ADA and WHO criteria respectively. The prevalence rates for females and males are similar at 12.1% (95% CI: 5%-21%). The pooled prevalence rates for urban and rural settlements are also similar at 9% (95% CI: 2%-22%). In conclusion, the prevalence of prediabetes in Nigeria is almost 2 times higher than the 7.3% estimate by the International Diabetes Federation in 2003. The similar rates of prediabetes between males and females and between urban and rural settlements points towards narrowing of cardiovascular risk burden between the two sexes and the two settlements. This represents higher future cardiovascular disease burden in the country further pressurizing the overstretched health care system.